Diagnostic evaluation of the enabling environment for private sector investment in Belize : final report (Trevor Hamilton and Associates KingstonJM)
Seeks to determine the extent to which the technical, policy, bureaucratic and legislative environment promotes private investment and enhances the competitiveness of business especially for export markets.
Bibliography: Appendix 2